The Way of Love according to Jesus (Jn 15:12-17) - Nguyễn, Kim Danh (Khoa Học Công Giáo và Đời Sống, 2022)
The two words "love" are frequently overused, especially among Christians. However, in John 15:12-17, Jesus teaches us a new way to love based on His own example. His new approach to love is to do what is best for others, to love truly, and to initiate romantic relationships. Accepting all gestures of love is the ultimate manifestation of divine love. Love is present everywhere and dominates everyone’s life. "Love one another" is also God's commandment. But love here is not love in a worldly way. People often only love those who love them, love those who seem to benefit them, and love according to their selfish nature. Jesus wants each of us to love one another as he has loved.